LEGAL PROTECTION OF THE CHILDREN ON VIOLENCE BY THE PARENTS (A Study in Demak) - Sugiharto Sugiharto; Jehan Bestari Amartiwi (Jurnal Pembaharuan Hukum, 2018)
The criminal act of domestic violence is very common talk among the public. Domestic violence often occurs due to several factors, among which are economic factors that occur in the household as was the case between husband and wife or parents and children. The method used is the juri dical methods of sociology with emphasis on research that was done on the real state of society. Research shows that the legal protection of children as victims of criminal acts of violence committed by parents in the region, namely Demak amicably and lega l action .